Solution-based fabrication of VO2 (M) nanoparticles via freeze drying - Thet Myat, Noe (2014)
Vanadium dioxide (VO2) has been receiving the attention of researchers due to its solar modulation ability through metal to insulator phase transition at 68 ˚C. Nanocomposite coatings fabricated by dispersing nanoparticles in dielectric matrix have been reported to provide improvement in thermochromic properties. Freeze drying assisted solution-based method was used to fabricate VO2 (M) nanoparticles. The size of nanoparticles and phase transition temperature can be tuned by varying the precursor concentration. Moreover, crystallinity of the nanoparticles can be improved by increasing the annealing temperature from 550 to 650 ˚C. The best combination of result was obtained from nanoparticles synthesized using 7.5 mL of H2O2 and annealed at 650 ˚C (particle size ≈ 190 nm, τc = 65.5 ˚C and LH = 31.85 J/g). From the results, it can be inferred that future studies with larger amount of solvent and higher annealing temperature may be useful in producing nanoparticles with smaller size. Increasing the milling strength and duration for nanoparticles before annealing may also help in reducing the particles size.